KOMUNIKASI INTERPERSONAL PERAWAT DENGAN LANSIA PANTI JOMPO UPT PSTW KHUSNUL KHOTIMAH DI KOTA PEKANBARU - Havifi, Ilham; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Interpersonal communication is very important in the interaction of a goodrelationship between the nurse with the elderly in a nursing home. Through interpersonalcommunication can nurses know how to build a good relationship with the elderly, causing asense of comfort for the elderly in old spends his days in a nursing home. The purpose of thisstudy is to explain how the effectiveness of interpersonal communication with the elderly andnurses know what interpersonal communication disorders among nurses with elderly in anursing home. The usefulness of this study are expected to contribute significantly to thedevelopment of science communication and serve as an input for further research.This research was conducted in a nursing home UPT PSTW Khusnul Khotimah Riauprovince, located on the road Kaharudin Nasution Pekanbaru. This research uses descriptivequalitative research methods that describe and interpret the data. Informants in this studywere nurses, the elderly, and the head of a nursing home by using techniques aimedinformants, purposiv. Data collection techniques using observation, interviews, anddocumentation.The results of this study indicate that braided interpersonal communication by thenurse with the elderly has been operating effectively in a nursing home UPT PSTW KhusnulKhotimah. The problems faced by elderly nursing elderly is a condition that is affected byvarious factors such as the elderly who are old age, the presence of the illness, the elderlywho are already emotionally unstable, elderly and their families feel left out so it is placed ina nursing home, which causes the elderly feel comfortable in his old days spent in a nursinghome. The effectiveness of interpersonal communication conducted with elderly nurse is ableto evoke the spirit, motivation, self-confidence and the elderly, in order to feel comfortable inelderly nursing home by considering five aspects, namely openness, empathy, positiveattitude, being supportive, and equality. Impaired interpersonal communication betweennurses with elderly include three things: physical disorders, psychological disorders, andsemantic disorders.Keywords : Interpersonal, Communication, Nursing Home